The effect of 6-week different resistance training on shooting performance among elite archers / Mohd Faridz Ahmad ... [et al.] - Ahmad, Mohd Faridz; Khairul Adnan, Muhammad Azfar; Md Japilus, Siti Jameelah; Adnan, Mohd Aizzat; Shahudin, Nurul Nadiah; Abdul Halim, Mohd Hafzal (Universiti Teknologi MARA, Perlis, 2024)
Archery is a sport that needs archers to shoot the arrows to the target by using a bow that requires muscular strength and endurance to form a proper technique to hit the target precisely. Therefore, the purpose of this study is to investigate the effects of 6-week different resistance training on shooting accuracy among archers. This study was carried out using an experimental research design. 12 men were recruited in this study and were divided into two groups; muscular strength training group (n = 6) and muscular endurance training group (n = 6). Both groups had undergone 6-week training program differently and had to perform pre- and post-shooting tests. The result showed that there was a significant increment in the shooting accuracy in muscular strength group (p = .000) and muscular endurance group (p = .001). This increment was reflected in the nature of the archers when they had to pull the string strongly and repeatedly during a game. In conclusion, the 6-week resistance training has had a positive influence towards archers’ shooting accuracy. Future studies are recommended to compare between elite and non-elite archers for new finding on accuracy.